A metafísica da noite no cinema de fluxo: a intuição do devir material nas paisagens durativas - Mariano, Guilherme Henrique Pereira (2023)
The present research aims to explore three main reflective movements. Firstly, we depart from the assumption of a new stage occupied by the cinema of flux, as defined by Oliveira Jr. (2010), within the 19th-century painting's revolution of landscape representation, as presented by Aumont (2004), by the continuity of the transformation of our perceptual relations with matter through these artistic expressions. Secondly, we contemplate a possible "metaphysics of the night," where the constant threat of non-being, proposed by Bachelard (2018), along with the concepts of duration and intuition, central theses in Bergson's philosophy (1974, 1999), offer a means to experience absolute material becoming. Lastly, we employ the films Toute une nuit (1982) by Chantal Akerman and Sábado à noite (2007) by Ivo Lopes Araújo as vehicles to interconnect the previously raised debates and, drawing from Sobchack's (1992) bodily cinematic theories, we propose new discussions to address the following question: Do the nocturnal urban landscapes of the cinema of flux possess the potential, just like the concrete experience of the night, to provide us with an intuition of the absolute duration of reality?